(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
Purpose: The purpose of this paper is to understand the relationship between HRM practices and Perceived Organisational Performance (POP) and also examine the role of employee work attitudes as mediator in influencing such relationship. Design/Methodology/Approach: Following a descriptive research design, an empirical investigation was carried out by approaching 300 respondents from regional rural banks in India to collect data through online survey forms as well as physical questionnaires. The research instruments was developed using five-point Likert-type scale and items for the construct in the study were taken based on literature review. The SPSS 21.0 and AMOS 21.0 were used for data analysis and hypothesis testing. Findings: It was found that HRM practices are positively related with organisational performance. In addition to this it was also revealed that work attitudes partially mediate the HRM-OP relationship. Originality/Value: The study is original in the sense that it provides insights into HRM practices and Organisational Performance relationship through the lens of work attitudes in regional rural banks. Implication: The study would be helpful for the concerned authorities in understanding HRM-PERFORMANCE mechanism, redesign HRM policies as employee centric, focus on social exchange relationship in an organisation to improve organisational performance. Management could think of providing department wise training so that employees could focus towards their specific department.